Defining long-term survivors in metastatic lung cancer: insights from a Delphi study in Spain - Carcereny, Enric; Domine, Manuel; Ortega Granados, Ana Laura (Frontiers in Oncology, 2025)
The improvement in survival rates in metastatic lung cancer (mLC) has increased the number of survivors’ special care needs. This study aimed to define and characterise these long-term survivors. A Delphi method with two successive rounds was conducted to reach a consensus (defined as an agreement ≥ 70%) on 56 items among 41 medical oncologists. The items included the definition of long-term survivors, their common characteristics, and oncological and non-oncological implications. The experts had an average age of 46 years, 53.7% were men, 90.2% attended for thoracic tumours, 40% had more than 15 years’ experience in mLC, and 56.1% of managing > 50 patients/month. Consensus reached 53.6% in the first round and 73.2% in the second. The definition of long-term survivors reached 58.3% consensus, defined as overall survival ≥ 3 years and/or progression-free survival ≥ 2 years. Identification of common features obtained 76.2% consensus on adenocarcinoma subtype of non-small-cell lung cancer, high PD-L1 expression, absence of brain metastasis, and fewer than two metastatic locations. Consensus was reached on specialized medical follow-up to detect immune-mediated toxicities and second neoplasms (87.8%), on pharmacological/non-pharmacological treatment for fatigue (82.9%) and sexual dysfunction (85.4%); and also on the importance of support for work and social adaptation (92.7%), integration of primary and hospital care (90.2%), implementation of quality-of-life programmes (92.7%) and electronic media (73.2%). This consensus identifies common characteristics and highlights relevant implications that should guide the follow-up and clinical management of these patients, ensuring better care and quality of life.